Information System Strategic Planning For Tourism Transportation Company Using Ward And Peppard Methodology - Prasetyo, Danianto Enggar; Wijaya, Agustinus Fritz (INTENSIF: Jurnal Ilmiah Penelitian dan Penerapan Teknologi Sistem Informasi, 2021)
Implementation of Information Systems in company business processes can increase efficiency and effectiveness. However, without adequate planning in the implementation of Information Systems, the performance can not have the desired impact. Therefore, a strategic plan is needed to implement the Information System aligned with the Company's vision and mission, and objectives. The method used in this research is the Ward and Peppard methodology. The background to the use of the Ward and Peppard methodology in this study is because the Ward and Peppard methodology contains a definitive and complete framework that focuses not only on technology but also on the organization's business needs. The results of this research are application recommendations and an application development roadmap for the next four years. It is hoped that this research can help improve the Company's business processes more effectively and efficiently by improving information management within an organization.